Leading for Sustainability in Crisis: MSMEs Evidence from Banten Indonesia - Marinus Gea; Sri Lestari (Yayasan Aya Sophia Indonesia, 2026)
MSMEs in Banten, Indonesia have faced unprecedented challenges during recent crises including the COVID-19 pandemic, economic disruption, and digital transformation pressures. While leadership's role in organizational resilience has received scholarly attention, how MSME leaders specifically enable sustainability practices under crisis constraints remains underexplored. This study investigates the mechanisms through which adaptive leadership facilitates sustainability practices in MSMEs operating under crisis conditions in Banten, Indonesia. Employing a qualitative interpretive approach, we conducted in-depth interviews with 18 MSME owner-managers and thematic analysis of crisis adaptation narratives. Findings reveal that crisis-responsive leadership operates through three integrated mechanisms: (1) strategic reorientation that reframes sustainability as cost-efficiency and stakeholder retention rather than compliance burden; (2) resource mobilization by leveraging community networks and informal financing; and (3) capability building through experiential learning and collective action. The study demonstrates that sustainability in crisis contexts is not a luxury but an adaptive strategy that enhances long-term viability. Novelty emerges in three dimensions: theoretically, by reconceptualizing sustainability as an outcome of adaptive leadership rather than a standalone management system; empirically, through detailed evidence from Indonesia's vulnerable MSME ecosystem; and methodologically, through interpretive analysis capturing the lived experiences of Banten MSMEs navigating simultaneous economic and digital disruptions. These findings offer practical guidance for MSME leaders and policymakers in designing context-responsive sustainability initiatives that strengthen resilience under persistent uncertainty.